LIFE INSURANCE MARKET IN UZBEKISTAN: ACHIEVEMENTS AND CHALLENGES (Academicia Globe: Inderscience Research, 2022)
This article discusses the importance of the life insurance industry, shows its historical formation in Uzbekistan and the main stages of development. A consistent analysis of changes in legislation and regulation of the life insurance industry reveals the methodological aspect of market research. and also considers the prospects and problems of old housing in Uzbekistan. Based on the analysis of the current state and development problems, proposals are made for the further development of the life insurance industry.